Dekolonisasi Studi Al-Quran: Sebuah Rekonstruksi atas Gagasan Joseph Lumbard - Idris; Fatkhiatus Su’adah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
Today, the trend of decolonization of science has spread to various disciplines, including in the field of Qur'anic studies. According to Joseph Lumbard's observation, al-Qur'an studies have so far been under the hegemony of Euro-American scholars. In the development of global Qur'anic studies discourse, Muslims do not have the power to explain their own holy book. The Qur'an and Muslims are only used as objects of knowledge. If there is a Muslim scholar who discusses the study of the Qur'an in the perspective of Islam itself, it is considered as a non-cognitive theological reading and unthinking comformity, which is a reading that cannot be included in the rational and objective thought process as carried out by modern scholars (Euro-Americans). If they want to explain the Qur'an, they must do so with the methods and approaches of Euro-American scholars. According to Lumbard, this phenomenon is caused by a feeling of superiority among Euro-American academics. He calls it the epistemic privileging of Euro-American approaches. This feeling of superiority then leads to an assessment that the Euro-American approach is more civilized than other approaches. Therefore, the hegemony of global knowledge discourse regarding al-Qur'an studies requires decolonization steps. He offers a decolonization idea that he calls trans-modern qur'anic studies. Namely, an idea that accommodates various backgrounds and various discourses that are cross-methodological and cross-epistemelogical.